A nonlinear M-estimation approach to robust asynchronous multiuser detection in Non-gaussian noise - Pham, DucSon; Zoubir, A.; Brcic, Ramon; Leung, Yee-Hong (IEEE Signal Processing Society, 2007)
A nonlinear M-estimation approach is proposed to solve the multiuser detection problem in asynchronous code-division multiple-access (CDMA) systems where the ambient noise is impulsive and the delays are not known. We treat the unknown delays as nuisance parameters and the transmitted symbols as parameters of interest. We also analyze the asymptotic performance of the proposed estimator and propose suboptimal but computationally efficient procedures for solving the nonlinear optimization function. Simulation results show considerable improvements over the conventional approaches.